GAMBARAN PERAN ORANGTUA SEBAGAI PEMBERI INFORMASI KESEHATAN REPRODUKSI REMAJA USIA 10-14 TAHUN DI KABUPATEN MALANG - Chusnah, Anuril Risma (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2023)
Abstract: The main problems of adolescent reproductive health (KRR) in Indonesia are the lack of information on reproductive health, shifts in adolescent sexual behavior, poor health services and unsupportive legislation. The problem is that parents who are considered experts and experienced have obstacles in sharing experiences due to socio-cultural factors. The purpose of this study was to identify the role of parents as providers of information on adolescent reproductive health in Petungsewu Village, Dau District, Malang Regency. The number of research samples was 88 respondents who were parents of teenagers aged 10-14 years in the village of Petungsewu, Dau District, Malang Regency. The research method uses descriptive. The sampling technique used is simple random sampling technique. Data collection using questionnaires. Data analysis was carried out using a descriptive. The results of this study are that most parents have a sufficient role in providing information about reproductive health of adolescents aged 10-14 years in Petungsewu Village, Dau District, Malang Regency, which is as much as 57%. Health workers are expected to increase education to parents regarding reproductive health of adolescents aged 10-14 years.Abstrak: Permasalahan yang paling utama kesehatan reproduksi remaja (KRR) di Indonesia, adalah kurangnya informasi mengenai kesehatan reproduksi, pergeseran perilaku seksual remaja, pelayanan kesehatan yang buruk serta perundang-undangan yang tidak mendukung. Permasalahannya, orang tua yang dianggap ahli dan berpengalaman, memiliki hambatan dalam berbagi pengalaman karena faktor sosio kultural. Tujuan dari penelitian ini adalah mengidentifikasi peran orangtua sebagai pemberi informasi kesehatan reproduksi remaja Desa Petungsewu , Kecamatan Dau, Kabupaten Malang. Jumlah sampel penelitian sebanyak 88 responden yang merupakan orangtua remaja usia 10-14 tahun di desa petungsewu Kecamatan Dau Kabupaten Malang. Metode penelitian menggunakan deskriptif. Teknik pengambilan sampel menggunakan teknik simple random sampling. Pengumpulan data menggunakan kuesioner. Analisis data dilakukan dengan deskriptif. Hasil penelitian ini adalah Sebagian besar orangtua berperan cukup dalam memberikan informasi seputar kesehatan reproduksi remaja usia 10-14 tahun Desa Petungsewu Kecamatan Dau Kabupaten Malang yaitu sebanyak 57%. Pada tenaga kesehatan diharapkan meningkatkan edukasi terhadap orangtua mengenai kesehatan reproduksi remaja usia 10-14 tahun.